Direct drug susceptibility testing of Mycobacterium tuberculosis to primary anti-tubercular drugs by nitrate reductase assay - Mishra Baijayanti; Muralidharan S; Srinivasa H (Wolters Kluwer Medknow Publications, 2009)
Objectives: Traditional drug susceptibility testing for Mycobacterium tuberculosis takes weeks and/or expensive. In this study, we evaluated nitrate reductase assay for drug susceptibility testing which is faster than the visual detection of colonies. Materials and Methods: 32 clinical specimens (direct microscopy positive for AFB with 1+, 2+ or 3+ grading) were decontaminated and the sediment was inoculated onto the L-J medium with INH or Rifampicin incorporated with Potassium nitrate and the same medium without antibiotics at 1;10 dilution as control. After 2 weeks, the control was first tested for color change with addition of nitrate reductase reagents. If found positive, the media with antibiotics were tested and compared. Futher incubation was done if the control was found to be negative. The results obtained was compared with standard direct proportion method for drug susceptibility testing. Results: Resistance of isolates as shown by both methods for INH and Rifampicin was 37.5% and 31.3% respectively. The results showed that NRA and proportion method do not differ significantly ( P < 0.05 for both drugs). Thus an excellent agreement between the results of NRA and proportion method was found for two primary anti-tubercular drugs, 87.5% for INH and 97% for Rifampicin. Conclusion: Nitrate reductase assay is a rapid and inexpensive method for susceptibility testing of M. tuberculosis for primary anti-tubercular drugs and could be an alternative to existing methods, particularly in resource poor settings.